Germany : 2007 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice; and Statement by the Executive Director for Germany. (IMF Staff Country Reports; Country Report ;, 2008)
The German economy has made major strides, helped by wide-ranging reforms. Greater transparency and stronger incentives for prudent action will support crisis prevention and management. The immediate priorities are preserving the integrity of the financial system and maintaining economic confidence. Policy on banking sector restructuring should be mindful of, and consistent with, the forces of international financial integration. Stepping up productivity is the key to sustaining growth. Further efforts are needed to bolster and reinforce commendable gains in fiscal outcomes.